Changes in the Microbiome During Chronic Rhinosinusitis - Mateusz de Mezer; Nina Chalama; Cheyanna Bratt; Melanie Kiebalo; Natalia Dolata; Jan Rogaliński; Małgorzata Leszczyńska (Pathogens)
Chronic rhinosinusitis (CRS) is a common inflammatory disease of the paranasal sinuses with a yet unknown etiology. As studies continue to elucidate the disease’s heterogeneity inflammatory profile and presentation, there is a growing interest in the influence of the nasal microbiome on disease pathogenesis and chronicity. The sinus microbiota appear dominated by the Staphylococcus and Corynebacterium genera; known upper airway pathogens, such as Haemophilus influenza, are present in the upper airways of healthy individuals, though at relatively lower abundances than in CRS patients. Viral culprits may induce an unhindered local immune response that contributes to the recurrence and chronicity of inverted papillomas—benign mucosal lesions with the propensity for local destruction and malignant transformation that can be found in patients with a history of nasal infection. The persistence of inverted papillomas warrants investigation into their pathogenesis and how they may contribute to a nasal landscape promoting the chronicity of CRS. Further investigation is needed to uncover the interplay between resident microbiota and viral, fungal, and immunological influence. Discerning between ‘healthy’ and ‘diseased’ sinonasal microbiomes and ‘keystone’ species could shed light on CRS etiology and provide the opportunity for CRS treatment tailored to an individual’s microbiome. This review aims to explore the interrelation of microbial residents in the pathogenesis and chronicity of the diseased sinonasal environment.